Stress corrosion cracking behavior of austenitic stainless steel in 3.5% NaCl solution - Mohd Firdaus Jaafar
Stress corrosion cracking is the formation of brittle cracks in a normally sound material through the simultaneous action of a tensile stress and a corrosive environment.